Health and Safety for You - Diehl, Harold S. (Harold Sheely), 1891-1973 (McGraw-Hill, 1980)
An introduction to anatomy, physiology, mental and physical health, preventive medicine, environment and heredity, safety, drugs, nutrition, human sexuality, and health careers.